Estudo dos mecanismos de transferência de tensões de cisalhamento em concreto fissurado com e sem reforço de fibras de aço: uma análise exploratória - Martins, Bárbara Gomes (2016)
The steel fiber-reinforced concrete have been widely used in concrete pieces to improve their mechanical properties. This research is performed an exploratory experimental analysis in order to assess the contribution of steel fibers in the shear strength of the concrete. A methodology for evaluation of the direct shear strength and the direct tension of the concrete is developed, as well as to evaluate the shear stress transfer mechanism by aggregate interlock. From the tests, it evaluates the influence of steel fibers in the transfer mechanism of shear stresses through the aggregate interlock pre-cracked plans of concrete. In the experimental development was used medium strength concrete (60 MPa), with 12.5 mm coarse aggregate varying the volume of steel fibers in 0%, 0.5% and 1.5%. The results showed that the methodology developed to evaluate the resistance to direct tensile work, but there needs some modification in the molding of concrete specimens with fibers to prevent the concentration of fibers in the specimen faces, which resulted in reducing the tensile strength of concrete. As for the direct shear test with two planes, the results showed that the test methodology worked well until the maximum force, showing a reduction in the shear strength of the concrete when compared to similar tests, but with fixed supports. Finally, the results of direct shear testing on pre-cracked (push-off test) showed that the fibers contribute significantly to the effect of aggregate interlock by reducing the opening of the crack and the sliding interface for a given shear stress.